2020
DOI: 10.1007/978-3-030-64861-9_60
|View full text |Cite
|
Sign up to set email alerts
|

Modified UTAUT2 to Determine Intention and Use of E-Commerce Technology Among Micro & Small Women Entrepreneurs in Jharkhand, India

Abstract: E-commerce revolution is creating enormous growth opportunities for IndianSMEs. Yet, reports suggest that adoption of e-commerce remains low among women entrepreneurs in the micro and small sector. This research applies a technology acceptance perspective to examine the determinants which induce the behavioral intention to accept and use ecommerce among the women entrepreneurs of Jharkhand, a developing state of eastern India. The UTAUT2 model of technology acceptance was modified to measure the relative impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…Facilitating condition is also one of the constructs that indicate the reason for using the technology. Consistent with Dutta and Shivani (2020) who found that there is a positive relationship between facilitating condition towards e-commerce usage. This construct explains the availability of facilities, infrastructures, or supportive environments that enable them to adopt the technology successfully.…”
Section: Facilitating Conditionsupporting
confidence: 79%
See 1 more Smart Citation
“…Facilitating condition is also one of the constructs that indicate the reason for using the technology. Consistent with Dutta and Shivani (2020) who found that there is a positive relationship between facilitating condition towards e-commerce usage. This construct explains the availability of facilities, infrastructures, or supportive environments that enable them to adopt the technology successfully.…”
Section: Facilitating Conditionsupporting
confidence: 79%
“…Facilitating conditions directly affect user behavior by providing the belief that the organization and infrastructure are available to support system usage. This is supported by Dutta and Shivani (2020) as well as Singh and Behl (2016) who found that facilitating conditions are crucial in assisting users in adopting technology.…”
Section: Unified Theory Of Acceptance and Usage Technologymentioning
confidence: 76%
“…Understanding the interplay between facilitating conditions and behavioral intention is essential in explaining the dynamics of technology adoption and can inform strategies to enhance technology acceptance in various contexts. According to Dutta and Shivani (2020), facilitating conditions have a significant positive influence on behavioral intention. This means that when women entrepreneurs have access to the necessary resources and infrastructure, it increases their intention to adopt and use ecommerce technology.…”
Section: Facilitating Conditions and Behavioural Intentionmentioning
confidence: 99%
“…The UTAUT2 model established by Venkatesh et al (2003) serves as the underpinning theory to investigate the factors influencing nanotechnology adoption and to develop a study framework and research hypotheses. UTAUT2 was chosen as the guiding principle because it has been used to understand technology adoption in a variety of industries, including healthcare (Bile Hassan et al, 2022), e-learning (Osei et al, 2022) and e-commerce (Dutta & Shivani, 2020). The UTAUT2 model, according to Addy et al (2022), is often employed as a theoretical framework for predicting technology adoption within an organisation.…”
Section: Theorymentioning
confidence: 99%